Molecular dynamics of targeting CD38 in multiple myeloma. (11th February 2021) - Malavasi, Fabio; Faini, Angelo C.; Morandi, Fabio; Castella, Barbara; Incarnato, Danny; Oliviero, Salvatore; Horenstein, Alberto L.; Massaia, Massimo; van de Donk, Niels W. C. J.; Richardson, Paul G.
Summary: Multiple functions of CD38 need exploring to expand clinical application of anti‐CD38 antibodies in multiple myeloma (MM). We investigated membrane dynamics of MM cells and subsequent events when CD38 is targeted by therapeutic antibodies. Human MM cells (BF01) were co‐cultured in vitro with therapeutic antibody (or control immunoglobulin G) and analysed using gene expression profiling. Microvesicles from antibody‐exposed cells were analysed for differential gene and microRNA (miRNA) expression, and for phenotypic characterisation. Exposure of BF01 cells to anti‐CD38 antibody resulted in CD38 membrane redistribution, upregulation of metabolism‐related genes and downregulation of genes involved in cell cycle processes. Microvesicles derived from antibody‐exposed cells showed increased CD73 and CD39 expression, presence of programmed death‐ligand 1 and significant up‐/down‐modulation of miRNAs. Microvesicles accumulated around immunoglobulin Fc receptor‐positive (FcR + ) cells. Upon internalisation, natural killer cells displayed significantly increased expression of genes related to activation and immune response, and downregulation of genes involved in the cell cycle. Cells may use microvesicles to transmit signals distally as part of a survival strategy. Microvesicles are equipped on their surface with enzymatic machinery leading to production of tolerogenic adenosine. Further, they are internalised in FcR + cells with significant functional modifications. These observations have relevance for improving anti‐CD38 therapeutic antibodies through targeting this mechanism and its sequelae.